2016
DOI: 10.1038/srep37117
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious processing of facial attractiveness: invisible attractive faces orient visual attention

Abstract: Past research has proven human’s extraordinary ability to extract information from a face in the blink of an eye, including its emotion, gaze direction, and attractiveness. However, it remains elusive whether facial attractiveness can be processed and influences our behaviors in the complete absence of conscious awareness. Here we demonstrate unconscious processing of facial attractiveness with three distinct approaches. In Experiment 1, the time taken for faces to break interocular suppression was measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 35 publications
6
48
1
Order By: Relevance
“…The eye-tracking results confirmed that the beautiful faces are strong attractors of attention [109], since participants spent about 10% more time dwelling onto the attractive face in a pair (Fig 5) than on the relatively less attractive one. It has been shown that the attentional priority towards attractive faces can also occur unconsciously [110] and that a decision about a face's level of attractiveness can be reached very rapidly (within 33 ms), and not very differently than when having unlimited time [111]. However, the present results are consistent with several previous studies showing that we typically spend extra time looking at faces considered attractive [112][113][114].…”
Section: Discussionsupporting
confidence: 92%
“…The eye-tracking results confirmed that the beautiful faces are strong attractors of attention [109], since participants spent about 10% more time dwelling onto the attractive face in a pair (Fig 5) than on the relatively less attractive one. It has been shown that the attentional priority towards attractive faces can also occur unconsciously [110] and that a decision about a face's level of attractiveness can be reached very rapidly (within 33 ms), and not very differently than when having unlimited time [111]. However, the present results are consistent with several previous studies showing that we typically spend extra time looking at faces considered attractive [112][113][114].…”
Section: Discussionsupporting
confidence: 92%
“…Recent research has provided evidence that facial attractiveness can be processed in the complete absence of consciousness [ 36 ], on account of the fact that attractive faces enjoyed the privilege of breaking suppression and reaching consciousness earlier. Therefore, it’s not hard to understand why contrastive effect and assimilative effect exist simultaneously because they have totally different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Face attractiveness, which is of great importance in interpersonal interaction, is a holistic visual trait that we often use to make first-pass assessments of people as we associate this feature with romantic viability, sociability, and health (see reviews [ 28 ]). Sequential biases on face attractiveness were prevalent [ 29 36 ], but they were little understood. Experiment 1 aimed to primarily find out whether face attractiveness ratings made in sequence were influenced by the true attractiveness values of the previous faces and the ratings given to the previous face.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, other bCFS studies showed that participants' own face (Geng et al, 2012, Experiment 1), faces with direct gaze (Chen & Yeh, 2012;Stein, Senju, Peelen, & Sterzer, 2011;Yokoyama, Noguchi, & Kita, 2013, Experiment 1), faces belong to familiar identities (Gobbini, Gors, Halchenko, Rogers, et al, 2013), faces oriented toward the observer (Gobbini, Gors, Halchenko, Hughes, & Cipolli, 2013) and faces, which are experienced in a congruent configuration (Moors, Wagemans, & de-Wit, 2016) overcome the suppression faster. In addition, Hung, Nieh, and Hsieh (2016) showed that in comparison to invisible unattractive faces, invisible attractive faces break the suppression faster (Experiment 1), have lower detection threshold (Experiment 2), and nonconsciously direct spatial attention (Experiment 3; also see Nakamura & Kawabata, 2018). Therefore, results from bCFS studies may indicate the survival of face recognition processes in the absence of awareness while employing CFS.…”
Section: Nonconscious Face Recognitionmentioning
confidence: 97%